Pemanfaatan Limbah Padat Cangkang Kelapa Sawit Menjadi Biooil Grade 2 - Azhar Basyir Rantawi; St. Nugroho Kristono; Gilberth Teguh (Politeknik Kelapa Sawit Citra Widya Edukasi, 2022)
Palm oil shell is a large palm oil processing wastes, reaching 60% of oil production. Utilization of oil palm shell biomass can be used for biopellets and biooil. Cellulose, hemicellulose, and lignin components in biomass are factors that affect the quantity and quality of biooil produced. This study aims to make grade 2 biooil from oil palm shells with the pyrolysis method, to determine the physical properties of biooil produced from oil palm shell pyrolysis. Palm oil shells can be converted into grade 2 biooil by pyrolysis method. Samples that are close to the parameters of the physical properties of biooil are actually obtained with a burning time of 1 hour and have a density of 1.0391 gr/cm with a pH of 2.91 and a grade 2 biooil with a density of 1.0038 gr/cm with a pH of 2.87. Analysis of grade 2 biooil with GC-MS identified 1.15 Pentadecanediol (C16H32O2) 37.603%; n-Hexadecanoic acid (C16H32O2) 18.923%; phenol (C6H6O) 28.961%.